Memayu Hayuning Bawana: Integrating Javanese Philosophical Wisdom into Sustainable Cultural Tourism in Yogyakarta - Rachmadi, Hari; Afif, Fuadi; Ramadhan, Noverinto Gilang Nuzul (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
This study explores Memayu Hayuning Bawana, a traditional Javanese philosophy that emphasizes harmony, sustainability, and ethical responsibility, as a guiding framework for cultural-based tourism development in the Special Region of Yogyakarta (DIY), Indonesia. In the face of increasing globalization and cultural commodification, this research investigates how local philosophical wisdom can serve as an alternative paradigm to mainstream tourism strategies that often neglect cultural authenticity and ecological integrity.nUsing a qualitative, descriptive-analytical approach, data were collected through literature reviews and in-depth interviews with key stakeholders, including tourism village managers, cultural practitioners, and policy authorities in Yogyakarta. Thematic analysis was employed to interpret the integration of Memayu Hayuning Bawana within three dimensions: cultural preservation, environmental sustainability, and community empowerment.nFindings indicate that applying this philosophy helps revitalize traditional practices such as batik-making and gamelan performances, supports ecotourism initiatives based on ecological balance, and fosters inclusive tourism models through community-based enterprises. However, challenges such as the commodification of culture, unequal benefit distribution, and superficial environmental efforts highlight the need for balanced and inclusive governance.